Why Statutory Union Recognition Is Bad Labour Policy: The North American Experience - Adams, Roy J. (Industrial Relations Journal, 1999)
The proposed British legislation is modelled on that of the United States which has been a clear failure in its stated goal of encouraging the practice and procedure of collective bargaining (Adams, 1993). It has instead perpetuated a culture of labour-management animosity that many other nations have 113been able, to their benefit, to overcome (Adams, 1995c).